"Effect of core stability exercises on low back pain" - CHARUMATHI,; GEETHA HARI PRIYA,; JIBU GEORGE VARGHESE, (International Journal of Pharma and Bio Sciences, 2016)
Low back pain is one of the commonest disorder seen worldwide. Muscular weakness and muscle imbalance are considered to be causes of low back pain. It has been stated by several researchers that exercise helps to treat low back pain (LBP) and prevent chances of recurrence by strengthening the core muscles of the spine. Forty five patients, with low back pain and age group between 35 and 55 years were randomly selected. Subjects were requested to perform the prescribed exercises for 4 days a week and it was continued up to 6 weeks duration. Outcome measures were to grade pain using NRS and disability by Oswestry disability questionnaire, pre-intervention and post- intervention. The collected data were tabulated and analysed statistically with the paired -‘t’ test. This study reveals that the core stability exercises with theratube can be used to decrease the pain of individuals suffering from low back pain and it can decrease the disability and improve over all activitiesa of the individuals. So, it may be suggested that this type of exercises can be used for individuals with low back pain.